[Healing the wounds [videorecording]. - Lazaro, Cheche (Quezon City Probe Productions, 1992)
An investigative report on the tragic story of the comfort women forced to have sex with Japanese soldiers during World War II.
VHS.
Keywords: Henson, Rosa Luna -- Interviews; Comfort women -- Philippines; World War II, 1939-1945 -- Personal narratives, Filipino